2022
DOI: 10.1007/s10067-022-06365-y
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of diabetes mellitus and rheumatic diseases amidst the COVID-19 pandemic: influence on the risk of infection, outcomes, and immune responses

Abstract: Outcomes of COrona VIrus in patients with rheumatic diseases (RDs) reported in various studies are heterogenous owing to the influence of age and comorbidities which have a significant bearing on the infection risk, severity, morbidity, and mortality. Diabetes mellitus (DM) and RDs are closely linked with underlying pathobiology and treatment of RDs affecting the risk for DM as well as the glycemic control. Hence, we undertook this narrative review to study the influence of DM on outcomes of COVID-19 in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…This dysfunction can reduce the ability of in ammatory cells like neutrophils and macrophages to perform essential functions such as chemotaxis, adhesion, and phagocytosis during in ammation [20]. As a result, the body's response to pathogenic bacteria may be slowed down, compromising human resistance [21]. This study found that the prevalence of diabetes in patients with Systemic In ammatory Response Syndrome (SIRS) was signi cantly higher at 36.96% compared to 10.27% in the non-SIRS group.…”
Section: Discussionmentioning
confidence: 99%
“…This dysfunction can reduce the ability of in ammatory cells like neutrophils and macrophages to perform essential functions such as chemotaxis, adhesion, and phagocytosis during in ammation [20]. As a result, the body's response to pathogenic bacteria may be slowed down, compromising human resistance [21]. This study found that the prevalence of diabetes in patients with Systemic In ammatory Response Syndrome (SIRS) was signi cantly higher at 36.96% compared to 10.27% in the non-SIRS group.…”
Section: Discussionmentioning
confidence: 99%
“…This result was expected due to the immunosuppressive condition that could entail diabetes treatment. Complementary, higher odds of hospitalization and mortality were identified among people living with diabetes [53] , possibly because of weak protective immune mechanisms at the humoral and cellular response levels.…”
Section: Discussionmentioning
confidence: 99%
“…Counts and proportions are reported for all other variables and compared between groups using χ 2 or Fisher's exact tests. Backward stepwise logistic regression was used to estimate adjusted OR and their 95% CIs for severe COVID-19 associated [19][20][21][22][23][24] were also included as candidates in the stepwise regression. A full model was first constructed containing all candidate variables and interactions, then the least significant variable was removed, and the model was fit again.…”
Section: Statistical Analysesmentioning
confidence: 99%